A brief survey of symmetry in mathematics - Mostow, G. D. (The National Academy of Sciences of the USA, 1996)
This paper presents a brief survey of the idea of symmetry in mathematics, as exemplified by some particular developments in algebra, differential equations, topology, and number theory.